Italia y Argentina. Novelas contemporáneas narran las migraciones decimonónicas - Magnani, Ilaria (Rassegna Iberistica, 2018)
It is only after the last years of the last century that the Italian and Argentine narratives have reconsidered migratory themes. This article compares two novels, Mar de olvido (1992) by the Argentine Rubén Tizziani and Tango alla fine del mondo (2013) by the Italian Diego Cugia, who share a common plot: the saga of an Italian family forced to emigrate to Argentina braided with an icon of argentinity such as tango. The analysis aims to show how a common interest and the use of analogous themes give rise to literary products aesthetically and ideologically very different. Historical circumstances, national origin, different writers intentions and readership shape literary results and national reception.